2023
DOI: 10.1002/adfm.202309871
|View full text |Cite
|
Sign up to set email alerts
|

A Porous Skeleton‐Supported Organic/Inorganic Composite Membrane for High‐Efficiency Alkaline Water Electrolysis

Yiwen Liao,
Guoxiong Deng,
Haoyu Wu
et al.

Abstract: Hydrogen energy is a truly renewable and clean energy source. Alkaline water electrolysis (AWE) is the most promising technology for green hydrogen production currently. In the AWE process, the critical part of an alkaline electrolyzer is the membrane, which acts to conduct hydroxide ions and block gases. However, developing low area resistance, high bubble point pressure and highly stable membrane for high‐performance AWE is still a challenge. Herein, porous skeleton‐supported composite membranes via the blad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Liao et al reported an improvement in the ion conductivity and dissolved hydrogen permeability of a skeleton-supported composite membrane (SSCM) by controlling the dispersion and pores of ZrO 2 nanoparticles, enhancing wettability and microstructure. The SSCM, by coupling the PSF, ZrO 2 nanoparticles, and polypropylene (PP) mesh, was fabricated via a blade coating method and the following pre-evaporation step . The pre-evaporation step was utilized to create a skin layer, enhancing the bubble point pressure of the SCCM.…”
Section: Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Liao et al reported an improvement in the ion conductivity and dissolved hydrogen permeability of a skeleton-supported composite membrane (SSCM) by controlling the dispersion and pores of ZrO 2 nanoparticles, enhancing wettability and microstructure. The SSCM, by coupling the PSF, ZrO 2 nanoparticles, and polypropylene (PP) mesh, was fabricated via a blade coating method and the following pre-evaporation step . The pre-evaporation step was utilized to create a skin layer, enhancing the bubble point pressure of the SCCM.…”
Section: Membranesmentioning
confidence: 99%
“…The SSCM, by coupling the PSF, ZrO 2 nanoparticles, and polypropylene (PP) mesh, was fabricated via a blade coating method and the following pre-evaporation step. 113 The pre-evaporation step was utilized to create a skin layer, enhancing the bubble point pressure of the SCCM. Consequently, the SSCM achieved an ultrahigh bubble point pressure of 27 bar and ultralow area resistance of 0.15 Ω cm 2 .…”
Section: ■ Membranesmentioning
confidence: 99%
“…In addition, especially for industrial applications, meeting crucial requirements such as high durability and enhanced performance as well as high gas purity is necessary. However, the physical and electrochemical assets of the membrane can be enhanced by forming composites that contain either polymer composites or both organic and inorganic compounds. …”
Section: Introductionmentioning
confidence: 99%
“…However, the physical and electrochemical assets of the membrane can be enhanced by forming composites that contain either polymer composites or both organic and inorganic compounds. 16 19 …”
Section: Introductionmentioning
confidence: 99%